Multiplex-PCR Detection of an Atypical Leuconostoc mesenteroides subsp. jonggajibkimchii Phenotype Dominating the Terminal Spoilage Microbial Association of a Fresh Greek Whey Cheese Stored at 4 °C in Vacuum - Nikoletta Sameli; Eleni Sioziou; Loulouda Bosnea; Spiros Paramithiotis; John Samelis (Applied Microbiology)
A species-specific multiplex-PCR method and phenotypic tests were combined to evaluate biochemical and genotypic differences between 24 representative Leuconostoc mesenteroides diverse isolates previously found to dominate in spoiled, vacuum-packed Anthotyros whey cheeses stored at 4 °C for 40 days and identified by 16S rRNA gene sequencing. Based on their phenotypic (API 50 CHL) profiles, the 24 isolates comprised 6 multi-strain and 7 single-strain biotypes. Only two single-strain biotypes (L4A and L4B) produced slime (dextran) from sucrose, and only four biotypes (L2A–L2C, L3; 7 isolates) fermented L-arabinose; the remaining 15 isolates (biotypes L1A–L1F) were dextran-negative, oligofermenting Ln. mesenteroides variants, able to ferment D-xylose and grow at 37 °C. Based on their multiplex-PCR (rpoB, araA, dsr, and sorA) gene profiles in comparison with those of the type strains of the four Ln. mesenteroides subsp. cremoris (rpoB), dextranicum (rpoB/dsr), mesenteroides (rpoB/araA/dsr/sorA), and jonggajibkimchii (rpoB/araA/dsr), no isolate was assigned to the first two subspecies and only four isolates (L2A and L2C) to the subsp. mesenteroides. Ten isolates shared the subsp. jonggajibkimchii profile, while the other ten ones have a fifth atypical profile (rpoB/dsr/sorA), seemingly being closer to the subsp. dextranicum. Particularly the atypical biotype L1B representatives of the most prevalent psychrotrophic Ln. mesenteroides subsp. jonggajibkimchii (rpoB/araA/dsr) genotype at Anthotyros whey cheese spoilage deserve further biochemical and molecular characterization studies.